Perilaku Konsumen Remaja Menggunakan Produk Fashion Bermerek Ditinjau dari Kepercayaan Diri - Wahyu Pranoto; Iranita Hervi Mahardayani (Jurnal Psikologi: PITUTUR, 2010)
This study aims to empirically examine the relationship between consumer behavior of teenagers using branded fashion products withconfidence. In this study the subjects of research is student in the Muria Kudus University, with a purposive sampling basedsampling that samples with characteristics of teenagers using branded fashion products. Measuring instrument used to obtain the data is scale consumer behavior teenagers use fashion branded products and the confidence scale. The results obtained from both the correlation coefficient rxy of 0.433 with p of 0.000 (p smaller than 0.050), this means there is a significant positive relationship on teenagersconsumer behavior using branded fashion products with confidence. So the hypothesis accepted. Teenangers consumer behaviorusing branded fashion product and confidence gained on medium category. Effective contribution to the behavior variable of consumer confidence at 43.3%.